Multifunctional Benzothiadiazole‐Based Small Molecules Displaying Solvatochromism and Sensing Properties toward Nitroarenes, Anions, and Cations1. Issue 6 (26th September 2014) - Alfonso, María; Espinosa, Arturo; Tárraga, Alberto; Molina, Pedro
Abstract Aryl or heteroaryl 5‐substituted imidazo‐benzothiadiazole derivatives were synthesized and shown to display remarkable solvatofluorochromism and selectively sense mercury(II) cations, acetate anions, and nitroaromatic derivatives, with discrimination between p‐nitrophenol and picric acid. These novel sensors are of importance these days, as the detection of explosives is a high priority in issues of national security and environmental protection. To determine the ion binding properties of the sensors, their absorption and fluorescence emission spectra upon binding different cations and anions were compared. Significant shifts in the spectra were only observed for mercury(II) and acetate. The binding of these two ions was further studied using 1H NMR. The binding properties of different nitroaromatic compounds were also determined, and the results showed the importance of the presence of a phenol group in the guest molecule. Specifically, the two sensors were shown to discriminate between p‐nitrophenol and picric acid. Finally, the mechanism of fluorescence quenching upon addition of nitrophenols was determined by computational methods.